2021
DOI: 10.1002/app.51286
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the hardener with latent and rapid curing based on phenol‐amine salts for applications to cyanate ester resins

Abstract: We have developed the curing agents that have good storage stability for cyanate ester resins. It should be noted that these agents can be given rapid and efficient curing at low temperatures around 100°C. Even though the nucleophilicity was reduced by a phenol‐amine salts consisting of basic aliphatic amines and weakly acidic phenols, the curing reaction with the cyanate ester occurred immediately. It means that the control of the curing reaction with cyanate esters is not easy due to the equilibrium between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…As an alternative to avoid these situations, alkylphenols such as nonylphenol are employed as cocatalysts, which can assist in melting such metal catalysts and promote cyclotrimerization . Metal complexes and hydrogen-donating cocatalysts for curing have been studied to improve efficiency and convenience to achieve the curing at a lower temperature. In recent studies, highly active organocatalysts that allow the curing reaction to proceed without the addition of a metal catalyst have been reported. We also found a thermal latent polymeric hardener that could cure cyanate ester resins rapidly at approximately 100 °C and had good storage stability with the resins using a phenol–amine salt …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As an alternative to avoid these situations, alkylphenols such as nonylphenol are employed as cocatalysts, which can assist in melting such metal catalysts and promote cyclotrimerization . Metal complexes and hydrogen-donating cocatalysts for curing have been studied to improve efficiency and convenience to achieve the curing at a lower temperature. In recent studies, highly active organocatalysts that allow the curing reaction to proceed without the addition of a metal catalyst have been reported. We also found a thermal latent polymeric hardener that could cure cyanate ester resins rapidly at approximately 100 °C and had good storage stability with the resins using a phenol–amine salt …”
Section: Introductionmentioning
confidence: 92%
“…15−18 We also found a thermal latent polymeric hardener that could cure cyanate ester resins rapidly at approximately 100 °C and had good storage stability with the resins using a phenol−amine salt. 19 On the other hand, cyanate ester resins have been applied as a matrix resin with epoxy resins, which are widely available industrially. The general curing reaction is shown in Figure S4.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that the thermal latent polymeric hardener based on phenol-amine salts (PAH) could undergo the rapid curing of epoxy resins/cyanate resins system and afford cured materials with high thermal stability and adhesiveness. [16][17][18] This PAH was formed by ionic and hydrogen-bonding interactions between polymeric phenols and amines. The curing process resulted in the disappearance of the interactions by heating and the melt of PAH into the resins.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 At the same time, due to the highly symmetrical structure of the triazine ring produced by the trimerization reaction of CE resin, the CE resin not only has a large volume shrinkage but also exhibits brittleness, which seriously affects the application of the CE resin in various fields. 5,6 In order to solve these problems, researchers proposed to blend or copolymerize with other resins by means of introducing irregular molecular structure, reducing the shrinkage related residual stress and the crack sensitivity, such as epoxy resin, 7,8 bismaleimide, 9,10 and benzoxazine. 11,12 It is well-known that benzoxazine is a novel developed phenolic resin, which has the characteristics of excellent thermal properties, low water absorption, no byproduct formation, and very low shrinkage during the curing process, and good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, CE resin has a fatal defect in that the curing temperature is very high, above 300°C, which cannot meet the industrial demands 3,4 . At the same time, due to the highly symmetrical structure of the triazine ring produced by the trimerization reaction of CE resin, the CE resin not only has a large volume shrinkage but also exhibits brittleness, which seriously affects the application of the CE resin in various fields 5,6 . In order to solve these problems, researchers proposed to blend or copolymerize with other resins by means of introducing irregular molecular structure, reducing the shrinkage related residual stress and the crack sensitivity, such as epoxy resin, 7,8 bismaleimide, 9,10 and benzoxazine 11,12 …”
Section: Introductionmentioning
confidence: 99%